WAYS TO PREVENT INFLATION THROUGH EFFECTIVE MANAGEMENT OF MONETARY POLICY - Shamsitdinova Xonzoda; Mirdjamalov Daler (Galaxy International Interdisciplinary Research Journal, 2023)
This article analyzes the scientific theoretical aspects of inflation, the aspects that are neglected in its prevention, and the dynamics of inflation in Uzbekistan and word practice.